1977
DOI: 10.1093/infdis/136.2.271
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Bacteriology of the Vaginal Flora

Abstract: Quantitative bacteriology was performed on vaginal secretions from healthy adult women. The analysis included a single sample from 17 college students and 35 samples from five volunteers collected at intervals of three to five days throughout the menstrual cycle. Mean concentrations in all 52 specimens were 10(8.1) aerobic bacteria/g and 10(9.1) anaerobic bacteria/g. The rank of predominant organisms, according to rates of recovery in concentrations of greater than 10(5) colony-forming units/g, was anaerobic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
84
1
4

Year Published

1980
1980
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(96 citation statements)
references
References 7 publications
7
84
1
4
Order By: Relevance
“…The incidence of the traditional aerobic components (lactobacilli, streptococci and coagulase-negative staphylococci) was not directly affected by the presence or absence of anaerobes. Very similar results on the dominance of anaerobes in the vaginal flora were obtained by Bartlett et al (1977) who found the mean concentrations of aerobes and anaerobes in 52 specimens from 22 healthy women to be 8-1 and 9.1 loglo cfu/ml of secretion. Recent qualitative studies using anaerobic techniques have also shown high isolation rates of anaerobes (Hill, 1980;Larsen and Galask, 1982).…”
Section: Discussionsupporting
confidence: 78%
“…The incidence of the traditional aerobic components (lactobacilli, streptococci and coagulase-negative staphylococci) was not directly affected by the presence or absence of anaerobes. Very similar results on the dominance of anaerobes in the vaginal flora were obtained by Bartlett et al (1977) who found the mean concentrations of aerobes and anaerobes in 52 specimens from 22 healthy women to be 8-1 and 9.1 loglo cfu/ml of secretion. Recent qualitative studies using anaerobic techniques have also shown high isolation rates of anaerobes (Hill, 1980;Larsen and Galask, 1982).…”
Section: Discussionsupporting
confidence: 78%
“…Bartlett et al (1977) detected relatively consistent mean levels of anaerobes and a significant decrease in concentrations of aerobes in premenstrual specimens from five women compared with those in the specimens collected in the week following onset of menstruation. However the converse effect was noted in a recent semiquantitative study of 15 volunteers in whom it was found that aerobic bacteria remained relatively consistent during the sampling times but there was marked variation in the concentration of anaerobic gram-positive bacilli, mainly lactobacilli.…”
Section: Discussionmentioning
confidence: 66%
“…Vaginal swab samples were collected by using the duplicate swab sampling technique for quantitative and qualitative microbiology (7). Briefly, the study nurse inserted two sterile cotton swabs simultaneously into the vaginal vault.…”
Section: Subjectsmentioning
confidence: 99%
“…Both swabs were transported to the microbiology laboratory for processing within 2 h. The preweighed swab and tube were reweighed, and the difference between the final weight (of swab and tube together) and the preswab weight (of swab and tube together) was recorded as the sample weight. This method has been validated for obtaining sample weight in previous studies (6,7,43). Two additional samples were obtained with sterile cotton swabs: one was used for measuring pH, making a smear for Nugent scoring, and detection of volatile amines, and the other swab was used for Trichomonas culture.…”
Section: Subjectsmentioning
confidence: 99%